2019
DOI: 10.3390/f10020128
|View full text |Cite
|
Sign up to set email alerts
|

Species Diversity Associated with Foundation Species in Temperate and Tropical Forests

Abstract: Foundation species define and structure ecological communities but are difficult to identify before they are declining. Yet, their defining role in ecosystems suggests they should be a high priority for protection and management while they are still common and abundant. We used comparative analyses of six large forest dynamics plots spanning a temperate-to-tropical gradient in the Western Hemisphere to identify statistical “fingerprints” of potential foundation species based on their size-frequency and abundan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
78
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(81 citation statements)
references
References 65 publications
3
78
0
Order By: Relevance
“…The plot harbors around 1,200 tree species, which makes of it one of the most diverse places on Earth (Duque et al, ). Eschweilera coriacea , Eschweilera itayensis , Eschweilera rufifolia , Otoba glycicarpa , Guarea pubescens and Rinorea lindeniana are important species in terms of basal area and abundance within the plot (Ellison et al, ). Soils in Amacayacu are acid (pH = 3.9 ± 0.1), with low contents of phosphorous ( p = 8.9 ± 0.1), and low total exchangeable bases (TEB = 1.2 ± 0.5) (Zuleta et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…The plot harbors around 1,200 tree species, which makes of it one of the most diverse places on Earth (Duque et al, ). Eschweilera coriacea , Eschweilera itayensis , Eschweilera rufifolia , Otoba glycicarpa , Guarea pubescens and Rinorea lindeniana are important species in terms of basal area and abundance within the plot (Ellison et al, ). Soils in Amacayacu are acid (pH = 3.9 ± 0.1), with low contents of phosphorous ( p = 8.9 ± 0.1), and low total exchangeable bases (TEB = 1.2 ± 0.5) (Zuleta et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Identifying foundation species is difficult because it can take many years—often decades— to collect enough data to distinguish foundation species from other species that also are common, abundant, or dominant ( sensu Grime, 1987) but lack “foundational” characteristics (Baiser et al, 2013; Ellison, 2014, 2019). Rather than investigating one common or dominant species at a time in myriad ecosystems, Ellison and his colleagues have worked with data from individual and multiple large forest dynamics plots within the ForestGEO network 1 to develop statistical criteria that can suggest which tree species might merit further attention as candidate foundation species in forests (Buckley et al, 2016 a , b ; Case et al, 2016; Ellison et al, 2019). Specifically, Ellison et al (2019) proposed two statistical criteria for candidate foundation tree species based on their size-frequency and abundance-diameter distributions, and on their spatial effects of on the alpha diversity (as Hill numbers: Chao et al, 2014) and beta diversity (e.g., Bray-Curtis dissimilarity) of co-occurring species.…”
Section: Introductionmentioning
confidence: 99%
“…When these foundation species decline or are selectively harvested, the landscape is homogenized and beta diversity declines. Indeed, Ellison et al (2019) suggested that the preservation of landscape diversity may be the most important reason to protect and manage foundation tree species before they decline or disappear.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations